2017
DOI: 10.1038/s41598-017-01456-2
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a nanobody specific to human pulmonary surfactant protein A

Abstract: Nanobody (Nb) is a promising vector for targeted drug delivery. This study aims to identify an Nb that can specifically target the lung by binding human pulmonary surfactant protein A (SP-A). Human lung frozen tissue sections were used for 3 rounds of biospanning of our previously constructed Nb library for rat SP-A to establish a sub-library of Nb, which specifically bound human lung tissues. Phage-ELISA was performed to screen the sub-library to identify Nb4, which specifically bound human SP-A. The binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Due to its abundant pulmonary expression but minimal expression in other tissues, SP-A is thought to be highly specific to the lung and thus can serve as an ideal target to the lung (Hamers-Casterman et al, 1993). Here, we used our previously developed nanobody to human lung SP-A (SPANb) (He et al, 2017), NSSLs as the drug delivery system, and MPS as the therapeutic drug to successfully prepare the human lung targeting GC drug MPS-NSSLs-SPANb (Figure 9). MPS-NSSLs-SPANb particles developed in the current study exhibit obvious advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its abundant pulmonary expression but minimal expression in other tissues, SP-A is thought to be highly specific to the lung and thus can serve as an ideal target to the lung (Hamers-Casterman et al, 1993). Here, we used our previously developed nanobody to human lung SP-A (SPANb) (He et al, 2017), NSSLs as the drug delivery system, and MPS as the therapeutic drug to successfully prepare the human lung targeting GC drug MPS-NSSLs-SPANb (Figure 9). MPS-NSSLs-SPANb particles developed in the current study exhibit obvious advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar surfactant protein A (SP-A) is expressed the most abundantly on type II alveolar epithelial cells whereas barely found in the extrapulmonary organs, and thus SP-A is believe to be the most ideal lung tissue target (Kuroki et al, 1998 ). In our previous study, we have successfully developed anti-rat SP-A Nbs (rSPANb) (Wang et al, 2015 ) and anti-human SP-ANbs (hSPANb) (He et al, 2017 ) and have found rSPANbs and hSPANbs target the rat lung and human lung tissues highly specifically. The current study aimed to use hSPANbs as the lung targeting molecule, the clinically commonly used GC hormone methylprednisolone (MPS), and nano-sterically stable liposome (NSSLs) as the drug delivery vector to first develop a GC hormone agent (MPS-NSSLs-SPANb) that specifically targets the human lung.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to immunohistochemistry, the permeabilization methods used in electron microscopy can affect the ultrastructure. The higher penetrability of nanobodies allows the use of milder permeabilization methods maintaining the ultrastructure [40,41]. In addition, and like in SRM, the use of nanobodies leads to a reduction in the linkage error and concomitant increase in image resolution.…”
Section: Track and Visualize Viral Proteinsmentioning
confidence: 99%